Pedagogical System of Formation of Interest in National and Artistic Values in Students Through Fine Arts - Norqo‘chqorova Rohila Ziyodullayevna (Genius Journals, 2022)
Fine art is a product of creativity that enriches both the spiritual and material world of man. The integration of national-artistic values, which have been formed in our country for centuries, into the minds of students, is considered important in the process of today's globalisation. This is aimed at bringing up young people in the spirit of love for the motherland by practicing the pedagogical skills of our teachers.
Keywords: creative imagination; artistic taste; national dignity; creative thinking